Pengaruh Corporate Governance, Ukuran Perusahaan, dan Kinerja Keuangan terhadap Pengungkapan Corporate Social Responsibility Perusahaan Indeks ESG Quality 45 IDX - Siti Marhamah; Siti Khomsatun; Ilham Ramadhan Ersyafdi (Economics and Business Faculty UNUSIA, 2025)
This study aims to obtain empirical evidence and analyze the influence of corporate governance, firm size, and financial performance on corporate social responsibility (CSR) disclosure. The research population consists of companies listed on the ESG Quality 45 IDX KEHATI Index. Using a purposive sampling technique, 21 companies were selected as the research sample for the 2021–2022 period. The independent variables examined in this study include board of directors size, board of commissioners size, audit committee, managerial ownership, firm size, liquidity, and profitability. This study adopts a quantitative-associative research design, employing panel data regression analysis as the analytical technique. The findings reveal that CSR disclosure is significantly influenced by managerial ownership—as a proxy for corporate governance—and liquidity—as a proxy for financial performance. In contrast, other corporate governance proxies (board of directors size, board of commissioners size, and audit committee), as well as firm size and profitability, are found to have no significant effect on CSR disclosure.